2011
DOI: 10.4061/2011/289032
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Development of Pt(111) Stepped Surfaces and Its Influence on Methanol Electrooxidation

Abstract: The progress in the preparation of new electrode surfaces by electrochemical treatments exhibiting high faradaic efficiencies towards industrial electrocatalytic processes has gained more attention in today's scientific community. Most of the papers report new catalysts dispersed on different substrates, but some fundamental studies required for electrochemical and physical characterizations are sometimes forgotten. In this paper, we make a full staging of two electrochemical treatments that can be conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The significance of the changes caused by cathodic corrosion is emphasized by comparing them to modifications caused by repeatedly cycling at predominantly anodic potentials 35 36 37 . These latter cycling procedures can modify electrode surfaces by repeatedly oxidizing and reducing platinum in experiments that typically last 5 –10 min.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the changes caused by cathodic corrosion is emphasized by comparing them to modifications caused by repeatedly cycling at predominantly anodic potentials 35 36 37 . These latter cycling procedures can modify electrode surfaces by repeatedly oxidizing and reducing platinum in experiments that typically last 5 –10 min.…”
Section: Discussionmentioning
confidence: 99%
“…The different ratios illustrate the fact that surface structure plays a key role in several electrocatalytic reactions. [13][14][15] Gomes et al showed that GEOR is sensitive to the orientation of Pt atoms at the surface by using single-crystal surfaces. [4] To understand how these superficial changes can affect the GEOR, we performed a voltammetric study in the presence of 0.2 m glycerol in the supporting electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…For Pt NPs, the intensity ratio between the 200 and 111 diffractions was 0.75, which was larger than the conventional bulk intensity ratio of 0.53 [JCPDS 87-0647]. 50 This indicated that the synthesized Pt NPs, which were primarily bound by 100 planes, are inclined to preferentially orient parallel to the supporting substrates. Pt 110 was found to be the most effective catalyst for the ORR in sulfuric acid electrolytes.…”
Section: Characteristics Of Cnbs With Au/pt Npsmentioning
confidence: 85%